Analysis of User Acceptance Using UTAUT2 Model in KAI Access Application - Dwi Rosa Indah; Arwin Permata Putra; Mgs Afriyan Firdaus (Jurnal Teknologi Informasi dan Pendidikan, 2022)
The convenience provided by mobile applications provides substantial opportunities for companies, especially those engaged in the service sector to improve performance and service to customers and get the best feedback as the value of the company's competitive advantage. This study aims to determine the factors that influence behavioral intention and use behavior in the KAI Access application using the UTAUT2 model for users of the KAI Access application. The variables used in this study are performance expectancy, effort expectancy, social influence, facilitating conditions, hedonic motivation, price value, habit, behavioral intention, and use behavior. The number of respondents who can be used for data analysis and processing in this study was 257 respondents, with details of 27 offline respondents and 230 online respondents. The data was obtained from the distribution of google forms through various social media and the distribution of questionnaires directly at the Kertapati Palembang train station. The research method uses quantitative methods and analytical techniques using validity and reliability tests with Rasch Modeling, Path Analysis, Classical Assumption Test, Anova Test, and Partial Test. The results of the study concluded that performance expectancy, facilitating conditions, hedonic motivation, price value, and habit affect the behavioral intention and use behavior of the KAI Access application. The most influential/significant variables are facilitating conditions, hedonic motivation, price value, and habit.